2009
DOI: 10.1016/j.jcps.2009.06.004
|View full text |Cite
|
Sign up to set email alerts
|

When thinking is beneficial and when it is not: The effects of thin and round advertising models

Abstract: This study addresses the advertising effectiveness of round and thin models. Integrating previous findings and theories, the authors predict and find that impulsive and reflective product evaluations as responses to thin and round advertisement models diverge. Specifically, four experiments indicate that impulsive product evaluations follow a priming logic, such that the beauty of the model spills over directly onto product evaluations; thin models thus produce more favorable implicit responses than do round m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 42 publications
1
27
0
Order By: Relevance
“…[this] implies that comparison relevance is determined by the social nature of perceivers and not necessarily by the social nature of the target." In line with this idea, the pattern of findings in the current studies 2 and 4 may be interpreted as a social comparison effect: exposure to beauty-enhancing products in an advertisement lowered consumers' self-evaluations in much the same way as exposure to thin models in advertisements has been found to lower self-evaluations (Häfner and Trampe 2009;Smeesters and Mandel 2006). It should be noted that the contrast effect typically observed after exposure to thin models seems a more general phenomenon than the social comparison effects reported in the current studies.…”
Section: Contribution and Implicationssupporting
confidence: 76%
“…[this] implies that comparison relevance is determined by the social nature of perceivers and not necessarily by the social nature of the target." In line with this idea, the pattern of findings in the current studies 2 and 4 may be interpreted as a social comparison effect: exposure to beauty-enhancing products in an advertisement lowered consumers' self-evaluations in much the same way as exposure to thin models in advertisements has been found to lower self-evaluations (Häfner and Trampe 2009;Smeesters and Mandel 2006). It should be noted that the contrast effect typically observed after exposure to thin models seems a more general phenomenon than the social comparison effects reported in the current studies.…”
Section: Contribution and Implicationssupporting
confidence: 76%
“…We simply do not know whether the use of pro-age models promotes or decreases positive self-esteem, both among their target audience (middle-aged women) and young adults. Contrary to the widespread assumption that young models have a universally negative impact on viewers, or that pro-age campaigns have a universally positive influence, they could have both positive and negative effects, depending on the match or mismatch between viewer age and model age (Häfner & Trampe, 2009;Häfner et al, 2008).…”
Section: Open Research Questionsmentioning
confidence: 78%
“…Future research should determine if the relationship between the effectiveness of campaign models and sales is mediated by viewers' self-esteem. Alternatively, any affect elicited by the models might spill over to the advertised products themselves, as observed by Häfner and Trampe (2009), who found that product evaluations were directly affected by thin and round models and mediated by campaign liking (rather than self-esteem). It might be possible to use realworld models with normal body shapes and average attractiveness and still modify consumer behaviour, just without any harmful affective consequences (cf.…”
Section: Limitationsmentioning
confidence: 99%
“…For example, one study used an affective priming task in combination with explicit attitude measures to examine the effect of skinny or full-figured models on product liking (Häfner & Trampe, 2009). Here, findings show a positive effect of skinny (versus full-figured) models on implicit product evaluations, but a negative effect on explicit product evaluations.…”
Section: Applications In Advertising Researchmentioning
confidence: 99%
“…The studies that found advertising to have a different impact on implicit than explicit attitudes (Carraro et al, 2010;Forehand & Perkins, 2005;Häfner & Trampe, 2009) can also be explained in terms of the different evaluative processes. In these studies, there were rather obvious cues that the intention of the advertisement was to persuade people (think about the celebrity voice-overs, the skinny models, and the negative campaigns of political candidates).…”
Section: What Attitude Dissociations Revealmentioning
confidence: 99%